Next-generation engineered microsystems for cell biology: a systems-level roadmap. Issue 6 (June 2022) - Sundaram, Subramanian; Chen, Christopher S.
Abstract : Engineered microsystems for in vitro studies of cultured cells are evolving from simple 2D platforms to 3D architectures and organoid cultures. Despite advances in reproducing ever more sophisticated biology in these systems, there remain foundational challenges in re-creating key aspects of tissue composition, architecture, and mechanics that are critical to recapitulating in vivo processes. Against the backdrop of current progress in 3D fabrication methods, we evaluate the key requirements for the next generation of cellular platforms. We postulate that these future platforms – apart from building tissue-like structures – will need to have the ability to readily sense and autonomously modulate tissue responses over time, as occurs in natural microenvironments. Such interactive robotic platforms that report and guide cellular events will enable us to probe a previously inaccessible class of questions in cell biology. Highlights: The tissue microenvironment – diverse cells, extracellular matrices (ECMs), soluble factors, physical forces, and their respective organizations – is dynamic and regulates cell fate and function. Engineered microsystems re-create relevant cues in vitro to experiment without the complex crosstalk within an organism. 3D fabrication advances are driving these microsystems from 2D to biomimetic 3D geometries. Organoid cultures are achieving organ-like cellular diversity. The combination of these two developments is proving to be powerful. Additive fabrication allows depositing cells and ECMs into large organotypic constructs with features greater than ~100 μm, whereas subtractive photoablation achieves micrometer-scale resolution but cannot position cells or ECMs. Next-generation engineered microsystems need to achieve both large-scale and fine resolution. Controlling cues noninvasively midculture using advances such as in optogenetics or magnetic actuation will help simulate rapid microenvironmental changes seen in development, regeneration, and disease.